2021
DOI: 10.9734/ijpss/2021/v33i1630537
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genetic Study on Native Pigeonpea Germplasm of Chhattisgarh for Yield Attributing Traits

Abstract: Aims: To find out genetic variation of pigeon pea Germplasms population on Chhattisgarh, with H. armigera, M. vitrata Larvae Population. Study Design: Augmented RBD Design in 4 block with 3 check varieties. Place and Duration of Study: College of Agriculture Raipur, IGKVV, Chhattisgarh. During Kharif 2019-2020. Methodology: The experimental materials were used 100 local landraces of Pigeonpea and three popular standard checks. The Morphological observations on various agro-morphological chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
4
3
0
Order By: Relevance
“…The variance analysis indicated, except for plant height, the existence of genetic variance in the traits primary branches, secondary branches, pod length, pod width, number of seed per pod, pods per plant, weight of 100 seed, and grain yield, in both environments; besides, it also showed genetic variance for days to flowering and days to maturity in environment II. Similar results have been reported by Pal et al (2018), Satapathy et al (2019), Gaur et al (2020), andPandey et al (2021). The precision of the experiments was evaluated by the coefficient of variation, which is considered low, medium and high, based on the evaluation criteria by Pimentel-Gomes ( 2009), who considers the values of coefficient of variation as low, when they are less than 10%, medium, when they are between 10 and 20%, and high, when they are between 20 and 30%.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The variance analysis indicated, except for plant height, the existence of genetic variance in the traits primary branches, secondary branches, pod length, pod width, number of seed per pod, pods per plant, weight of 100 seed, and grain yield, in both environments; besides, it also showed genetic variance for days to flowering and days to maturity in environment II. Similar results have been reported by Pal et al (2018), Satapathy et al (2019), Gaur et al (2020), andPandey et al (2021). The precision of the experiments was evaluated by the coefficient of variation, which is considered low, medium and high, based on the evaluation criteria by Pimentel-Gomes ( 2009), who considers the values of coefficient of variation as low, when they are less than 10%, medium, when they are between 10 and 20%, and high, when they are between 20 and 30%.…”
Section: Resultssupporting
confidence: 92%
“…The estimates of genetic parameters that make it possible to infer the feasibility of using selective practices, as well as their effectiveness, were determined for all traits (except for plant height and grain yield) exhibiting high heritability (above 75%), indicating an association between phenotypic and genotypic values in both environments (Table 2). Similar results were reported by Pandey et al (2021) and Sharma et al (2021), who observed high heritability for primary branches, secondary branches, days to flowering, days to maturity, pod length, pod width, number of seed per pod, pods per plant, and weight of 100 seed. Pal et al (2018) observed high heritability for days to flowering, days to maturity and weight of 100 seed.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…(g) all are not significantly different from each other. Similar analysis was also done by Pandey et al [12].…”
Section: Resultssupporting
confidence: 71%